2023
DOI: 10.3390/ijms24108772
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Natural Products in the Improvement of Cancer-Associated Cachexia

Abstract: The enormous library of natural products and herbal medicine prescriptions presents endless research avenues. However, the lack of research evidence and trials on cancer-induced cachexia limit the therapeutic potential of natural products. Cancer-induced cachexia is a systemic wasting syndrome characterized by continuous body weight loss with skeletal muscle and adipose tissue atrophy. Cancer cachexia is a problem in itself and reduces the quality of life by lessening the treatment efficacy of anticancer drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 113 publications
(142 reference statements)
0
3
0
Order By: Relevance
“…The only drug approved for the treatment of cancer cachexia is an endogenous ligand, anamorelin hydrochloride, for the growth hormone release-promoting factor receptor (Garcia-Castillo et al, 2023;Watanabe and Oshima, 2023). To be noted, the treatment of cancer cachexia with herbal medicine has developed rapidly in recent years, and an increased number of active components in herbal medicine had been found to be potential anticachexia agents (Shankar et al, 2021;Han et al, 2023). In our previous study, a bioactive diterpene compound which was found in Lamiaceae spp., carnosol (CS), performed preferable mitigating effects on cancer cachexia-associated muscle atrophy in C26 cancer cachexia model mice (Lu et al, 2021).…”
Section: Introductionmentioning
confidence: 93%
“…The only drug approved for the treatment of cancer cachexia is an endogenous ligand, anamorelin hydrochloride, for the growth hormone release-promoting factor receptor (Garcia-Castillo et al, 2023;Watanabe and Oshima, 2023). To be noted, the treatment of cancer cachexia with herbal medicine has developed rapidly in recent years, and an increased number of active components in herbal medicine had been found to be potential anticachexia agents (Shankar et al, 2021;Han et al, 2023). In our previous study, a bioactive diterpene compound which was found in Lamiaceae spp., carnosol (CS), performed preferable mitigating effects on cancer cachexia-associated muscle atrophy in C26 cancer cachexia model mice (Lu et al, 2021).…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, the prostaglandins derived from EPA are less pro-inflammatory than those produced using arachidonic acid [ 34 ]. FAs have also been shown to reduce acute phase proteins such as C-reactive protein in different types of cancer [ 20 , 21 ].…”
Section: Natural Anti-inflammatories and Their Derivativesmentioning
confidence: 99%
“…The supplements are not intended to treat, diagnose, cure or alleviate the effects of the disease as per the regulations of the Food and Drug Administration and so are not regarded as pharmacological therapy [ 19 ]. Therefore, the benefits are that they are often cost-effective, readily available and generally well-tolerated [ 20 ].…”
Section: Introductionmentioning
confidence: 99%